2014
DOI: 10.1002/ana.24070
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome contributes to inflammation after intracerebral hemorrhage

Abstract: Objective The NLRP3 (NALP3, cryopyrin) inflammasome, a key component of the innate immune system, facilitates caspase-1 and interleukin (IL)–1β processing, which amplifies the inflammatory response. Here, we investigated whether NLRP3 knockdown decreases neutrophil infiltration, reduces brain edema, and improves neurological function in an intracerebral hemorrhage (ICH) mouse model. We also determined whether mitochondrial reactive oxygen species (ROS) governed by mitochondrial permeability transition pores (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
224
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 250 publications
(233 citation statements)
references
References 44 publications
9
224
0
Order By: Relevance
“…This is consistent with observations reported after spinal cord injury [47]. After intracerebral hemorrhage, NLRP3 inhibition reduced the inflammatory response, suggesting also an important function for this type of inflammasome [48]. …”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with observations reported after spinal cord injury [47]. After intracerebral hemorrhage, NLRP3 inhibition reduced the inflammatory response, suggesting also an important function for this type of inflammasome [48]. …”
Section: Discussionsupporting
confidence: 91%
“…The types of inflammasome activated in the brain may also depend upon the nature of the injury. For example, in a mouse model of intracerebral hemorrhage the NLRP3 inflammasome is reported to drive brain edema and behavioral deficits (52). It was reported recently that heme, a breakdown product of blood, activates the NLRP3 inflammasome (53).…”
Section: Discussionmentioning
confidence: 99%
“…In a model of unilateral uretral obstruction, heme and the active forms of caspase-1 and IL-1β are increased (63). It has been demonstrated that inflammation, renal dysfunction, and death triggered by transient renal artery occlusion, a model of tubular necrosis induced by ischemiareperfusion, was dependent on NLRP3 (53), and intracerebral hemorrhage also activates the NLRP3 inflammasome in a mechanism dependent on mtROS (65). We observed that the pathogenesis of hemolysis was dependent on inflammasome components, demonstrated by the high resistance of mice lacking Nlrp3, Asc, or Caspase-1.…”
Section: Discussionmentioning
confidence: 99%